PPARγ/SOD2 Protects Against Mitochondrial ROS-Dependent Apoptosis via Inhibiting ATG4D-Mediated Mitophagy to Promote Pancreatic Cancer Proliferation - Nie, Shuang; Shi, Zhao; Shi, Mengyue; Li, Hongzhen; Qian, Xuetian; Peng, Chunyan; Ding, Xiwei; Zhang, Shu; Lv, Ying; Wang, Lei; Kong, Bo; Zou, Xiaoping; et al. (Frontiers in Cell and Developmental Biology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is an extremely aggressive disease with poor prognosis. Our previous study found that peroxisome proliferator activated receptor gamma (PPARγ) was capable of enhancing glycolysis in PDAC cells. However, whether PPARγ could promote PDAC progression remains unclear. In our present study, PPARγ was positively associated with tumor size and poor prognosis in PDAC patients. Functional assays demonstrated that PPARγ could promote the proliferation of pancreatic cancer cells in vitro and in vivo. Additionally, flow cytometry results showed that PPARγ decreased mitochondrial reactive oxygen species (mitochondrial ROS) production, stabilized mitochondrial membrane potential (MMP) and inhibited cell apoptosis via up-regulating superoxide dismutase 2 (SOD2), followed by the inhibition of ATG4D-mediated mitophagy. Meanwhile, the activation of PPARγ might reduce pancreatic cancer cell stemness to improve PDAC chemosensitivity via down-regulating ATG4D. Thus, these results revealed that PPARγ/SOD2 might protect against mitochondrial ROS-dependent apoptosis via inhibiting ATG4D-mediated mitophagy to promote pancreatic cancer proliferation, further improving PDAC chemosensitivity.